Plant Polyphenols and Oxidative Metabolites of the Herbal Alkenylbenzene Methyleugenol Suppress Histone Deacetylase Activity in Human Colon Carcinoma Cells - Isabel Anna Maria Groh; Chen Chen; Claudia Lüske; Alexander Thomas Cartus; Melanie Esselen (Journal of Nutrition and Metabolism)
Evidence has been provided that diet and environmental factors directly influence epigenetic mechanisms associated with cancer development in humans. The inhibition of histone deacetylase (HDAC) activity and the disruption of the HDAC complex have been recognized as a potent strategy for cancer therapy and chemoprevention. In the present study, we investigated whether selected plant constituents affect HDAC activity or HDAC1 protein status in the human colon carcinoma cell line HT29. The polyphenols (−)-epigallocatechin-3-gallate (EGCG) and genistein (GEN) as well as two oxidative methyleugenol (ME) metabolites were shown to inhibit HDAC activity in intact HT29 cells. Concomitantly, a significant decrease of the HDAC1 protein level was observed after incubation with EGCG and GEN, whereas the investigated ME metabolites did not affect HDAC1 protein status. In conclusion, dietary compounds were found to possess promising HDAC-inhibitory properties, contributing to epigenetic alterations in colon tumor cells, which should be taken into account in further risk/benefit assessments of polyphenols and alkenylbenzenes.